2019
DOI: 10.3390/ijerph16224524
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric, Cardiopulmonary and Metabolic Benefits of the High-Intensity Interval Training Versus Moderate, Low-Intensity or Control for Type 2 Diabetes: Systematic Review and Meta-Analysis

Abstract: This study aims to evaluate the effectiveness of high-intensity interval training compared with no intervention and other types of training interventions for people with Type 2 diabetes. A systematic review and meta-analysis of randomized controlled trials that used high-interval intensity training to improve anthropometric, cardiopulmonary and metabolic conditions were conducted. The search was performed during October–December 2017 using the databases PubMed, Web of Science and Physiotherapy Evidence Databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 41 publications
3
25
0
2
Order By: Relevance
“…: increase in resting heart rate and body fat, dysregulation of insulin and glucose secretion, decrease in the levels of GLUT-4 transporter, loss of training-induced improvements in cholesterol and HbA1C levels) and functional consequences (i.e. : reduction of aerobic, muscle strength, flexibility, balance and agility performance) after short periods of interruption of aerobic and/or resistance exercise programs (24)(25)(26)(27)(28)(29). It is important to note that the potential requirement of cocooning (a more severe form of physical distance measures) or FIGURE 2 | Estimated cases of diabetes and all-cause mortality attributed for physical inactivity, before and after COVID-19 pandemic.…”
Section: Physical Inactivity During Covid-19 Outbreak and Its Impact mentioning
confidence: 99%
See 3 more Smart Citations
“…: increase in resting heart rate and body fat, dysregulation of insulin and glucose secretion, decrease in the levels of GLUT-4 transporter, loss of training-induced improvements in cholesterol and HbA1C levels) and functional consequences (i.e. : reduction of aerobic, muscle strength, flexibility, balance and agility performance) after short periods of interruption of aerobic and/or resistance exercise programs (24)(25)(26)(27)(28)(29). It is important to note that the potential requirement of cocooning (a more severe form of physical distance measures) or FIGURE 2 | Estimated cases of diabetes and all-cause mortality attributed for physical inactivity, before and after COVID-19 pandemic.…”
Section: Physical Inactivity During Covid-19 Outbreak and Its Impact mentioning
confidence: 99%
“…Regarding to prevention and treatment of diabetes, lifestyle interventions are recommended to be based on a well-structured physical activity program (physical exercise) and a healthy nutritional behavior (13), and physical exercise is essential for improving glycemic control, insulin signaling, blood lipids, low-grade inflammation, vascular function, body composition and others health variables (35). Systematic reviews with meta-analysis have showed that most of above mentioned benefits of physical exercise can be obtained by aerobic and/or resistance exercise programs (25,(36)(37)(38)(39). For example, a recent-meta-analysis of 37 studies involving 2208 individuals with diabetes showed that both supervised aerobic or resistance exercise were effective for promoting substantial improvements in HbA1C, total cholesterol and triglycerides; however, only aerobic exercise improved fasting plasma glucose and low-density lipoprotein cholesterol, while only resistance exercise improved systolic blood pressure (37).…”
Section: Physical Exercise For Managing Diabetes and Counteracting Dementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, sprint interval training (SIT) is another type of interval training usually performed at intensities equal to or greater than the pace that would elicit a peak in VO2 33 . There is accumulating evidence from meta‐analysis and systematic reviews supporting improved cardiometabolic health in overweight/obese and T2D, 34,35 decreased fat‐mass in adults, 36 enhanced aerobic capacity in healthy, young people, 37 and vascular function in patients 38 following HIIT. However, currently, no studies have comprehensively examined the effect of HIIT on inflammatory cytokines and adipokines 34,38 for which effects have been mixed 39‐42 .…”
Section: Introductionmentioning
confidence: 99%